Strong Sensitivity of Pine Island Ice-Shelf Melting to Climatic Variability - Dutrieux, Pierre; de Rydt, Jan; Jenkins, Adrian; Holland, Paul; Ha, Ho Kyung; Lee, Sang Hoon; Steig, Eric; Ding, Qinghua; Abrahamsen, E. Povl; Schroder, Michael (Science, 2014)
Pine Island Glacier has thinned and accelerated over recent decades, significantly contributing to global sea-level rise. Increased oceanic melting of its ice shelf is thought to have triggered those changes. Observations and numerical modeling reveal large fluctuations in the ocean heat available in the adjacent bay and enhanced sensitivity of ice-shelf melting to water temperatures at intermediate depth, as a seabed ridge blocks the deepest and warmest waters from reaching the thickest ice. Oceanic melting decreased by 50% between January 2010 and 2012, with ocean conditions in 2012 partly attributable to atmospheric forcing associated with a strong La Niña event. Both atmospheric variability and local ice shelf and seabed geometry play fundamental roles in determining the response of the Antarctic Ice Sheet to climate.